Subordinasi dan objek seksual: Representasi perempuan Bali dalam dua cerpen Indonesia tentang sabung ayam - I Wayan Artika (Pusat Kajian Bali Universitas Udayana, 2017)
This article examines tajen (cockfighting) and representation of Balinese women in two short stories, “Tajen” (Faisal Baraas, 1971) and “Tajen Terakhir” (Gde Aryantha Soethama, 2016). This topic was chosen because in the world of tajen men are represented of having the absolute power over Balinese women. Selected descriptive qualitative approach, intertextuality approach, and parallel reading data analysis method. Problem solved with new historicism theory. Data in the form of literary text and nonliterature text about tajen. The nonliterature texts as a co-text, such as Balinese folklore, traveling report, Balinese cockfighting manuscript, and research report about tajen. The results concluded three points. First, the world of tajen represented in both short stories were dynamic constellation of a number of aspects, such as male/gambler, betting, rooster, and victory obsession. Second, the obsession with the victory is above family, wife, and children matters. Third, women in the world of tajen become subordinate and sexual objects of men. The tragic fate of women in the world of tajen occurs because of the practice of patriarchy ideology.